Assessment of immunological markers and booster effects of Ag85B peptides, Ag85B, and BCG in blood of BCG vaccinated children: a preliminary report - Husain, Aliabbas A. (Clin Exp Vaccine Res, 2016)
PURPOSE: In the present study, the protective immunological markers in serum and peripheral blood mononuclear cells (PBMCs) of bacillus Calmette–Guérin (BCG) vaccinated and unvaccinated children were evaluated after vaccination. Further, PBMCs of children with low protective levels were boosted with BCG, Ag85B, and Ag85B peptides to study their booster effects to increase waning BCG induced immunity. MATERIALS AND METHODS: Fifty children from 1 month to 18 years of age were randomized for the study. Blood samples were collected from 27 participants with/without BCG vaccination. Immunological markers (anti-BCG, interferon γ [IFN-γ], and adenosine deaminase activity) were assessed in both serum and PBMCs of children. Children with low levels of protective immunological markers were further recruited and their PBMCs were boosted with BCG, Ag85B, and Ag85B peptides. RESULTS: Children in age group of 4-6 years were associated with significantly (p<0.05) higher BCG-specific IgG and IFN-γ levels compared to those in age group greater than 10 years. Vaccinated children had greater repertoire of immunological memory which on in vitro stimulation with BCG showed increase in BCG-specific response compared to unvaccinated controls. Assessment of booster effects of BCG, Ag85B, and Ag85B peptides in PBMCs of children revealed greater potential of peptides to boost BCG induced immunity compared to BCG and Ag85B. CONCLUSION: To conclude, children within age 4-6 years are associated with high immunological markers which eventually diminish with age thereby suggesting need for booster dose in later years. Mycobacterium tuberculosis peptides along with BCG may be used as attractive candidates to boost such waning BCG induced immunity in children.